Pengaruh Work Life Balance, Kepemimpinan Konvensional, dan Lingkungan Eksternal terhadap Produktivitas Karyawan di PT Mas Arya Semarang - Tania Wulandari; Sukirman Sukirman (PENG: Jurnal Ekonomi dan Manajemen, 2026)
The objectives of this study are: 1) To analyze the effect of work-life balance on employee productivity; 2) To analyze the effect of conventional leadership on employee productivity; 3) To analyze the effect of the external environment on employee productivity; and 4) To analyze the simultaneous effect of work-life balance, conventional leadership, and the external environment on employee productivity. This study employs a quantitative approach with a population of 556 individuals. The sampling technique used is the Slovin formula, resulting in a sample size of 150 respondents. Data were analyzed using an inferential approach via SPSS software, utilizing the multiple linear regression analysis method. The research results indicate that: 1) Work-life balance has a positive and significant effect on employee productivity; 2) Conventional leadership has a positive but insignificant effect on employee productivity; 3) The external environment has a positive and significant effect on employee productivity; and 4) Work-life balance, conventional leadership, and the external environment simultaneously have a significant effect on employee productivity.